Effectiveness of pretrial decisions on the implementation of confiscation and its legal implications - Ricky Indra Gunawan (Ius Poenale, 2020)
Pretrial is a control over the actions of investigators and public prosecutors in carrying out their duties and authority in the criminal justice process whether it has been done properly or not. The method used in this paper is a method with a juridical approach to Empirical and Normative Juridical.  The effectiveness of pretrial efforts towards the implementation of the confiscation process according to the researchers 'level of effectiveness is still questionable because as far as researchers' observations are concerned with the influence of the Constitutional Court's ruling, no community has yet filed a pretrial suit related to searches and seizures carried out by law enforcers. / PUU-XII / 2014 more people filed lawsuits for judicial petition related to the determination of suspects, this is evidenced by the number of pretrial claims against the determination of suspects and the implications in pretrial decisions regarding the implementation of foreclosures with the ruling Number 21/PUU-XII / 2014  , where the confiscation action is the tip of the investigator's action in order to prove the trial, so with the decision Number 21/PUU-XII/ 2014, the implications of the investigator are required to be more careful and  lam foreclosure. The implication is also in this case that the judge in deciding and considering a pretrial object in the form of confiscation in a case will also certainly have different views because the judge can interpret the law as long as the ruling of the Constitutional Court Number 21 / PUU-XII / 2014 which stipulates the seizure as a pretrial object has not been determined explicitly in the legislation.